A Study and review of Freelancer Value Proposition - Chandra Arifianto; Michael Vallentino (Kusuma Negara Business School, 2022)
This study aims to determine the value proposition for freelancers or freelancer value proposition (FVP). These values ​​include the value of work-life balance, autonomy, economy, development, hedonic, and social. The approach used in this research is qualitative. Interviews, observations and documentation were used for data collection which were applied to 5 informants. Data triangulation and interview reduction methods were used to analyze the data. The results of this study show that there are many insights into understanding the value proposition of freelancers. There are findings in the form of freelancers who can regulate work-life balance. Economically freelancers can improve their economic side. Freelancers have freedom (autonomy) in making decisions in their work tasks. In the value of development, there is an increase in skills when changing jobs, although for others it is difficult to get a career path. Hedonic, freelancers feel satisfied when they establish relationships and high wages. Expanded relationships and experience will give freelancers a good reputation socially.